MyOnline passport challenges to elderly or 'Warga Emas' assessment satisfaction / Rohana Ismail - Ismail, Rohana (2014)
The main strategy is to strengthening public sector ICT Governance and for support strategies are enhancing capacity and capabilities, enhancing performance measurement capabilities and strengthening policy enforcement through one of e-Government services is MyOnline Passport. E-Services facility provided the Immigration Department to facilitate the process of passport renewal in accordance with departmental direction towards creating a silent office. Passport MyOnline provided through the department's official portal online http://www.imi.gov.my connection with the Passport Department in 63 offices throughout Malaysia passport manufacturer. Passport MyOnline also benefit from access to the Myldentity system as a reference fingerprint and photo images of origin. The system also adopted the latest ePayment modules like Credit Card and FPX interbank fund transfer. When we talk about enhancing about capacity and capabilities, the key concepts are about to improve some business organizations consider business planning and business strategy as one of the most important aspects in their organization or MyOnline Passport in the future. The research objective get the positive input base on the conducted training to elderly or 'Warga Emas'. The research also base on the qualitative and observation to analyses of the user satisfaction and example model is Dynamic Model as guideline. With the comment, complaint and suggestion during training session will be main part to improve and enhance the system application and become first Human Computer Interactive (HCI) website system application in government sector.